Festival Cisadane Sebagai Atraksi Wisata Budaya di Kota Tangerang - Edison, Emron; Muchtar, Arisman; Nurzaini, Shakira Annisa (Manajemen dan Pariwisata, 2025)
This study aims to describe the Cisadane Festival as a cultural tourism attraction in Tangerang City using a qualitative method through literature review, observation, and documentation. The findings indicate that the Cisadane Festival, which originated from the Peh Cun tradition and was formalized in 1991, plays a multidimensional role as a medium for preserving tradition, a space for multicultural social interaction, a driver of the local economy, and a tourism promotion strategy. The festival features a variety of activities such as cultural performances, water sports competitions, MSME product exhibitions, traditional culinary showcases, and modern entertainment that blend harmoniously, thereby strengthening Tangerang City’s image as a cultural destination representing the acculturation between Chinese and local traditions. Considering its historical value and iconic character, the Cisadane Festival needs to be preserved and held consistently from year to year as a form of commitment to safeguarding cultural heritage and strengthening Tangerang City’s tourism identity.